2017
DOI: 10.1177/0960327117722821
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of diffusion-weighted magnetic resonance imaging performed in the acute phase as an early predictor of delayed neuropsychiatric sequelae in acute carbon monoxide poisoning

Abstract: Delayed onset of neuropsychiatric symptoms after apparent recovery from acute carbon monoxide (CO) poisoning has been described as delayed neuropsychiatric sequelae (DNS). No previous study has determined whether early use of diffusion-weighted magnetic resonance imaging (DWI) can predict which patients will develop DNS in the acute CO poisoning. This retrospective observational study was performed on adult patients with acute CO poisoning consecutively treated over a 17-month period. All included patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…In patients with CO poisoning, it was found that there was a 10-26% finding in MRI in the long term, and this rate was reported to be 14 times higher than those that developed acutely (9,(11)(12)(13) (8). In our study, neurological findings were detected in 10.4% of the patients, and MRI findings were detected in 40.6% of these patients.…”
Section: Discussionsupporting
confidence: 42%
“…In patients with CO poisoning, it was found that there was a 10-26% finding in MRI in the long term, and this rate was reported to be 14 times higher than those that developed acutely (9,(11)(12)(13) (8). In our study, neurological findings were detected in 10.4% of the patients, and MRI findings were detected in 40.6% of these patients.…”
Section: Discussionsupporting
confidence: 42%
“…Initial conscious disturbance is a known risk factor of DNS development [1,2,4]. However, Kim et al [5] reported that the Glasgow Coma Scale had 80% sensitivity and 77% specificity, which renders it unsuitable as a predictor in this case. Currently there are only a small number of parameters that are deemed useful in predicting DNS [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Since MRI can diagnose brain damage from CO poisoning, DNS may be more likely to occur in patients with ABLM. Recent studies have proposed that lesions on MRI, especially on DWIs, can predict DNS [ 18 , 34 ]. However, differences in the locations or patterns of MRI lesions have not revealed any correlations with DNS [ 13 ].…”
Section: Discussionmentioning
confidence: 99%